“Absence makes the heart grow fonder”: Linguistic and Social Experiences of Immigrant Students in Brazil - Fabielle Rocha Cruz; Rahat Zaidi (Journal of Research in Social Sciences and Language)
This study explores the impact of plurilingualism on the academic and social experiences of immigrant students in Curitiba, Brazil, utilizing Critically Engaged Language and Literacy Workshops (CELLWs). This research employed arts-based methodologies within CELLWs to probe into the experiences and identities of sixteen immigrant students enrolled in a Brazilian Portuguese as an Additional Language class. CELLWs are designed to foster not only language development but also cultural integration, using critical literacies to challenge and expand the participants' understanding of their new social environments. Drawing on data from CELLWs activities, initial findings reveal that these workshops fostered opportunities for immigrant students to connect their linguistic repertoires with personal and collective identities, enhancing their sense of belonging and agency. The findings provide insights into how educational settings can better support immigrant students, highlighting the role of critical literacies and arts-based research in enhancing educational inclusivity and effectiveness.